Research proposals and participation in European innovative projects through the eyes of ethics experts - Fanaras (Βασίλειος Φανάρας), Vasilios; Mollaki (Βασιλική Μολλάκη), Vasiliki (Bioethica, 2020)
Funding of research proposals by the European Commission (EC) requires not only scientific ex cellence and innovation, but also ethical conduct of research. For this reason, the EC performs ethics review for all the research proposals that are going to be funded, in order to check compliance with the ethics principles of research, as well as the Eu ropean and National laws, in the countries where research is conducted. The aim of the present manuscript is to raise awareness and familiarize researchers with the ethics review of research proposals, as conducted in the EC, through the eyes of two ethics experts. Firstly, the stages of the ethics review process are described, which is performed with the assistance of independent ethics experts. The criteria which are provided and monitored by the Ethics and Research Integrity Sector in the EC are then pr esented in detail. Based on these criteria, the possible outcomes of an ethics review are analyzed, which may include the formation of specific requirements that need to be fulfilled by the researchers. Specific reference is made to the requirements that m ay result when a research proposal involves collection, processing and storage of personal data according to the General Data Protection Regulation 2016/679, because this Regulation entered into force recently in the ethics review. Finally, reference is m ade to the importance of ensuring integrity in research thought the ethics review process, and the necessary compliance with the ethics standards of EC funded research.